Exploring the Short-Term Impacts of a Community-Based Book Distribution Program. Issue 2 (3rd April 2019) - Anderson, Kimberly L.; Atkinson, Terry S.; Swaggerty, Elizabeth A.; O'Brien, Kevin
ABSTRACT: This article presents findings from the first year of a multiyear investigation of the implementation of the Dolly Parton Imagination Library (DPIL) book distribution program as part of one community's long-term initiative to improve early literacy skills. The authors describe (a) the study's logic model and associated theory of change, (b) findings and their connection to the short-term outcomes in the model, and (c) findings-based adjustments to the model. When compared to parent reports from the baseline year, Year 1 parents of rising kindergartners reported greater frequency of shared book reading (SBR), greater engagement with their children during SBR, and greater children's interest in being read to. Findings also revealed the need for additional strategies to support DPIL enrollment and maximize family SBR experiences.